Analisis Faktor Yang Mempengaruhi Permintaan Sepeda Motor di Kota-Kota Besar Jawa Barat - Acuviarta Acuviarta; Arya Mukti Purnayaksa Permana (Jurnal Riset Ilmu Ekonomi, 2022)
The development of transport has affected economic transactions. The existence of adequate transportation facilities has supported economic mobility. But in reality not all public transport is reachable to the public. More affordable means of transportation are more in demand by the public. Especially in Indonesia, motorcycles are still a popular transportation that is in demand. This study aims to examine various factors that can affect the demand for motorcycles in major cities, West Java. Researchers observed the coverage area in the big cities of West Java, namely the cities of Bogor, Bandung, and Cirebon. This research uses quantitative research with secondary data sources. The demand for motorcycles as a dependent variable, then the number of population, the price of motorcycles, the interest rate and per capita income as independent variables. The results of this study show that the variables of population number and per capita income have a positive and significant influence on the demand for two-wheeled transportation. Meanwhile, the variable price of two-wheeled transportation and interest rates have a negative and significant influence on the demand for two-wheeled transportation